Evidence of vertical abundance stratification in the SB1 star HD 161660: a new HgMn. Issue 3 (12th October 2020) - Catanzaro, G; Giarrusso, M; Munari, M; Leone, F
ABSTRACT: In this paper, we present a detailed spectroscopic study of the SB1 system HD 161660. New spectroscopic observations have been obtained by us with Catania Astrophysical Observatory Spectropolarimeter (CAOS@OAC). Combining these observations with archive data from HARPS@3.6ESO, we derived atmospheric parameters as temperature and gravity (from the fit of Balmer lines), microturbulence and rotational velocity (from metal lines), and chemical composition. We found underabundances of helium, carbon, magnesium, sulphur and chromium, overabundances of neon, phosphorus, argon, manganese, xenon, and mercury. All other elements have solar composition. In particular, mercury abundance is derived taking into account an isotopic mixture different from the terrestrial one (essentially pure 202 Hg). Considering this chemical pattern, we definitively confirm HD 161660 is an HgMn star. Further, variability of equivalent widths points out a non-homogeneous distribution of helium and magnesium over stellar surface. As to iron and phosphorus, we found a non-constant abundance with the optical depth, a result currently considered an evidence of vertical stratification. Finally, we improved the fundamental parameters characterizing the HD 161660 orbit.